2019
DOI: 10.1161/strokeaha.119.025105
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Knowledge and Perceptions of Stroke in Rural Malawi

Abstract: Background and Purpose— The incidence of stroke in Malawi is unknown but major risk factors, including hypertension, obesity, and diabetes mellitus, are highly prevalent. We sought to understand community-level knowledge about stroke. Methods— A population-based cross-sectional study was conducted in rural Malawi (2016–2017). Adults aged ≥15 years were randomly selected and interviewed about their knowledge and perceptions of stroke symptoms, risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…This is consistent with the results of a range of studies in which low education level has been the factor most associated with a low level of knowledge in the population surveyed about stroke [19,[31][32][33]. Similarly, other investigations have confirmed an association between a higher level of education and a good state of knowledge [12,[34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the results of a range of studies in which low education level has been the factor most associated with a low level of knowledge in the population surveyed about stroke [19,[31][32][33]. Similarly, other investigations have confirmed an association between a higher level of education and a good state of knowledge [12,[34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…Unlike the poor perception of stroke reported in previous studies among patients in Nigeria 16 and even in community-based studies in Malawi 30 and Tanzania 31 majority of the respondents in this study had a good aggregate knowledge (84%) of Stroke and they (87.5%) knew stroke as a disease of the blood vessels in the brain which is consistent (87.4%) with the findings of the study done in Sokoto Nigeria 16 . The majority of the healthcare workers (93.5%) in this study knew that stroke is a preventable disease.…”
Section: Discussionsupporting
confidence: 84%
“…Social media includes newspapers, television, and online social media platforms. Some communities in Malawi believe that witchcraft was the reason for stroke and were unaware of the actual risk factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, protection from CVDs was perceived in the presence of medication adherence. Perceived seriousness and susceptibility to CVDs were reported as low to average across various studies [ 8 , 18 , 19 ]. Another study reported that perceived susceptibility to heart disease was related to destiny [ 8 ].…”
Section: Discussionmentioning
confidence: 99%